2016
DOI: 10.1107/s2052520615023690
|View full text |Cite
|
Sign up to set email alerts
|

Charge density of the biologically active molecule (2-oxo-1,3-benzoxazol-3(2H)-yl)acetic acid

Abstract: (2-Oxo-1,3-benzoxazol-3(2H)-yl)acetic acid is a member of a biologically active class of compounds. Its molecular structure in the crystal has been determined by X-ray diffraction, and its gas phase structure was obtained by quantum chemical calculations at the B3LYP/6-311++G(d,p) level of theory. In order to understand the dynamics of the molecule, two presumably soft degrees of freedom associated with the relative orientation of the planar benzoxazolone system and its substituent at the N atom were varied sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 43 publications
1
2
0
Order By: Relevance
“…The molecular conformations in both solids are associated with the same energetically favourable region in the PES, and only a slight trend towards a more planar overall geometry in the crystal than in the gas phase may be perceived. We have previously encountered good agreement between gas-phase and solid-state conformations (Mouhib et al, 2011;Nguyen & Stahl 2011;Wang et al, 2016), and this match has been confirmed even for the more controversial cases of biphenyl and cyclobutane (Cruz -Cabeza et al, 2012).…”
Section: Theoretical Results On O-nitrobenzoic Acidsupporting
confidence: 56%
“…The molecular conformations in both solids are associated with the same energetically favourable region in the PES, and only a slight trend towards a more planar overall geometry in the crystal than in the gas phase may be perceived. We have previously encountered good agreement between gas-phase and solid-state conformations (Mouhib et al, 2011;Nguyen & Stahl 2011;Wang et al, 2016), and this match has been confirmed even for the more controversial cases of biphenyl and cyclobutane (Cruz -Cabeza et al, 2012).…”
Section: Theoretical Results On O-nitrobenzoic Acidsupporting
confidence: 56%
“…Recent studies (Gleiter & Haberhauer, 2017 considered the complicated cases of bonding between chalcogen atoms, including two-, three-and four-center bonds. The other studies covered aspects of bonding in biologically important molecules such as the drug metronidazole with a diazole heterocycle in its structure (Kalaiarasi et al, 2019), polymorphs of famotidine based on a thiazole ring (Overgaard & Hibbs, 2004) and (2-oxo-1,3benzoxazol-3(2H)-yl) acetic acid (Wang et al, 2016). The electron density point of view on halogen bonds has been thoroughly presented in the recent works dealing with the NÁ Á ÁI bond (Wang et al, 2018), interactions in tetrafluorodiiodobenzene (Wang et al, 2019) and short ClÁ Á ÁCl bonding (Wang et al, 2012(Wang et al, , 2017.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, further searching of the strategies should rely on the knowledge of the benzoxazole system itself. One such example with a relatively strong O–H···O hydrogen bond [in (2-oxo-1,3-benzoxazol-3­(2 H )-yl)­acetic acid] has been recently studied in terms of experimental electron density. In such systems, the role of interactions with iodine in the progress of halocyclization cannot be underestimated. , …”
Section: Introductionmentioning
confidence: 99%